2016
DOI: 10.1177/0165025416644077
|View full text |Cite
|
Sign up to set email alerts
|

Temperament in the classroom

Abstract: Based on the emotion socialization and bioecological models, the present study examined the contributions of teacher emotion socialization (i.e., teacher reactions to child emotions) on children's social-emotional behaviors, and the moderating effect of child temperamental surgency on these relations in the preschool context. A total of 337 children and 80 teachers from private and public preschools/childcares participated in the study. To account for the nested nature of our data, hierarchical linear modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Moreover, after the PedaSens intervention, these children were more emotionally connected and more initiative to the ECPs. This is an encouraging result, considering that these children seem to be less oriented to teacher-child interactions in the classroom (Bassett et al 2017).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Moreover, after the PedaSens intervention, these children were more emotionally connected and more initiative to the ECPs. This is an encouraging result, considering that these children seem to be less oriented to teacher-child interactions in the classroom (Bassett et al 2017).…”
Section: Discussionmentioning
confidence: 68%
“…It seems that these children are learning social-emotional behaviour by observing interactions in the classroom, highlighting the role of the teacher for children's socio-emotional behaviour. On the contrary, high-surgency children's active orientation to ongoing activity and peer relationships may reduce the children's awareness of teacher-child interactions (Bassett et al 2017). This may result in a decrease in learning experiences about social-emotional behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, results suggest that teachers may have perceived children with high negative affectivity as closer to themselves. An explanation of this finding could be that children with negative affectivity may feel that they should be closer to teachers to meet their emotional needs or teachers may perceive these children as they need extra support in their https://doi.org/10.15405/epsbs.2019.11.63 Corresponding Author: Elsa Escalante Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 545 classroom (Bassett et al, 2016). Therefore, teachers may have seen children's negative affectivity in a positive way in their relationships with them within Colombian early childhood educational context.…”
Section: Resultsmentioning
confidence: 99%
“…Children learn to regulate their own emotions and become aware of the emotions of others through the ways in which teachers nurture, model, and respond to their feelings in the classroom (Denham et al, 2012; Pianta, 1999). For example, teachers have been observed to support preschoolers in regulating intense emotions (Silkenbeumer et al, 2018), and children make greater gains in observed emotion regulation when preschool teachers use more supportive and less unsupportive reactions to children’s emotions (Bassett et al, 2017). Whereas teachers’ observed sensitivity has been associated with growth in directly assessed emotion regulation for young children attending early Head Start programs (Mortensen & Barnett, 2019), teacher-reported conflict in kindergarten has been linked to children’s expression of more negative emotions in first grade, both in the classroom and during lunch/recess (Hernandez et al, 2016).…”
Section: Emotion Regulation Is Undergirded By Inhibitory Controlmentioning
confidence: 99%